Incidence of Central Venous Catheter-Related Bloodstream Infections: Evaluation of Bundle Prevention in Two Intensive Care Units in Central Brazil - Thais Yoshida; Ana Elisa Bauer de Camargo Silva; Luciana Leite Pineli Simões; Rafael Alves Guimarães (The Scientific World Journal)
Background. Central venous catheter-associated bloodstream infections (CVC-BSIs) have been associated with increased length of hospital stay, mortality, and healthcare costs, especially in intensive care units (ICUs). The aim of this study was to evaluate the incidence density of CVC-BSIs before and after implementation of the bundle in a hospital of infectious and dermatological diseases in Central Brazil. Methods. A retrospective cohort study was conducted in two ICUs (adult and pediatric) between 2012 and 2015. Two periods were compared to assess the effect of the intervention in incidence density of CVC-BSIs: before and after intervention, related to the stages before and after the implementation of the bundle, respectively. Results. No significant reduction was observed in the incidence density of CVC-BSIs in adult ICU (incidence rate ratio [IRR]: 0.754; 95.0% CI: 0.349 to 1.621; p-value = 0.469), despite the high bundle application rate in the postintervention period. Similarly, significant reduction in the incidence density in pediatric ICU has not been verified after implementation of the bundle (IRR: 1.148; 95.0% CI: 0.314 to 4.193; p-value = 0.834). Conclusion. Not significant reduction in the incidence density of CVC-BSIs was observed after bundle implementation in ICUs, suggesting the need to review the use of process, as well as continuing education for staffs in compliance and correct application of the bundle. Further studies are needed to evaluate the effect of bundle in the reduction of incidence density of CVC-BSIs in Brazil.